Synthesis of chirally pure 1-deoxy-d-xylulose-5-phosphate : A substrate for IspC assay to determine M. tb inhibitor - Edagwa, Benson J. (2013)
1-Deoxy-D-xylulsose-5-phosphate (DXP) is a key intermediate in the non-mevalonate or methyl erythritol phosphate (MEP) pathway for the biosynthesis of isoprenoid, which are essential building blocks involved in the construction of pathogens growth. Since the homologous enzymes of this pathway are not present in vertebrates, including humans, the MEP pathway presents a viable source for antimicrobial drug targets. However, an insight into the features of the enzymes involved in this pathway has been plagued by lack of chirally pure substrates. Here in, we report an efficient synthesis of enantiomerically pure 1-deoxy-D-xylulose-5-phosphate from commercially available 1,2-O-isopropylidene-α-D-xylofuranose through Weinreb amide formation in shorter route.